Argentine Beef Demand and Household Choices of Retail Channels - Rossini, Gustavo Eduardo (2014)
Household choices of outlet retail channels in beef purchases depend on several characteristics related to the quality of the product, convenience and ease of purchase, and economic factors such as price, income and payment methods. The aim of this paper is to study the influence of demographic and socio-economic attributes in the choice made by argentine consumers using a Multinominal Logit Model. The results show that the total number of purchases, the type of household, payment methods, and gender and schooling years of household head are the most relevant variables in the sample.